Conscious representations, intentionality, judgements, (self) awareness and qualia - Peruš, Mitja (Informatica (Ljubljana), 1998)
The problem of consciousness is discussed by considering on theories of mental representations, judgements, feelings and a subject's self-aware qualitative experiences. These characteristics of consciousness are correlated with materialistic background processes, except qualia which have, as it is argued, no obvious connection with naturalistic explanatory framework
Keywords: duševni procesi; zavest; samozavedanje; nevrobiologija; nevronske mreže